MENGURAI PERAN GANDA PEMERINTAH DAERAH DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN (STUDI KRITIS DI KAWASAN WISATA TAWANGMANGU) - Purwanti, Purwanti; Samsi, Samsi; Yitno Puguh Martomo; Harjono, Harjono (Bajang Institute, 2025)
Sustainable tourism development poses a significant challenge for local governments in maintaining a balance between economic, social, and environmental interests. However, the multiple roles played by local governments often face structural and operational obstacles. This study aims to critically examine how the Karanganyar Regency Government fulfills its roles as a motivator, facilitator, and dynamizer in promoting sustainable tourism in the Tawangmangu tourism area. This research employs a qualitative approach using a case study strategy, collecting data through in-depth interviews, participatory observation, and documentation involving informants from government agencies, tourism managers, business actors, and tourists. Data analysis follows the interactive model of Miles, Huberman, and Saldana. The findings indicate that the facilitator role is the most dominant in tourism development efforts, while the roles of motivator and dynamizer are present but not yet optimal. Supporting factors include natural potential, local cultural richness, and policy support, while the main obstacles consist of limited budget allocation, weak cross-sector coordination, and low public awareness of environmental issues. The study concludes that strengthening multi-stakeholder collaboration and integrating cross-sectoral policies are strategic steps to ensure the sustainability of tourism in Tawangmangu